2019
DOI: 10.1186/s12903-019-0895-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact evaluation of a school-based oral health program: Kuwait National Program

Abstract: Background This study evaluated the relationship between enrolment in a school-based oral health prevention program (SOHP) and: 1) children’s dental health status and oral health-related quality of life (OHRQoL), and 2) mothers’ oral health (OH) knowledge, attitude, practice, and OHRQoL. Methods This cross-sectional study, in the Kuwait Capital, included 440 primary school children aged 11 to 12 years and their mothers. Participants were classified into two groups: SOHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
0
17
0
14
Order By: Relevance
“…The nding highlights gross de ciencies of the schools in promoting oral health among adolescents. It also contrasts other ndings where supervised school brushing, preventive services and treatment services among other activities are components of the school oral health program [24][25][26]. It is also noteworthy that less than 30% of the schools had bene tted from such programs and about 20% of the students had participated in such programs.…”
Section: Discussionmentioning
confidence: 80%
“…The nding highlights gross de ciencies of the schools in promoting oral health among adolescents. It also contrasts other ndings where supervised school brushing, preventive services and treatment services among other activities are components of the school oral health program [24][25][26]. It is also noteworthy that less than 30% of the schools had bene tted from such programs and about 20% of the students had participated in such programs.…”
Section: Discussionmentioning
confidence: 80%
“…These findings are endorsed by various researches conducted in different regions. For instance, the research of Alsumait et al (2019) on the Kuwaiti primary students showed that oral health programs at an early age help induce effective oral hygiene practices. Similarly, another study of Ahmad (2019) also endorses school as an effective place for teaching oral health care practices.…”
Section: Discussionmentioning
confidence: 99%
“…Kuwait is one of the few countries in the Gulf region, where comprehensive national oral health surveys were conducted by the School Oral Health Program (SOHP) in 1982(SOHP) in , 1985(SOHP) in , 1993(SOHP) in , and 2001. These surveys assessed the dental health status of children aged 5-15 years (Alsumait et al 2019). In 1985, an oral health survey was conducted to ascertain the status of oral health in the whole population of Kuwait.…”
Section: Periodontal Diseases In the Gcc Regionmentioning
confidence: 99%